Potential nurses' action in confronting tuberculosis treatment in the family health strategy (Research, Society and Development, 2021)
Objective: To analyze the nurse's coping in the treatment of tuberculosis. Method: This is a descriptive, qualitative research, which sought to discuss studies in the field of nursing that contemplated the theme focused on patients diagnosed with tuberculosis, carried out on the Virtual Health Library (VHL) portal, as follows: Literature Latin American and Caribbean Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE), Scientific Electronic Library Online (SciELO), and Nursing Database (BDENF). Development: Factors related to treatment adherence and the user/professional bond and Fundamental elements for this user to receive the correct treatment. Considerations: The research aims to analyze the care provided by nurses in the care provided to people diagnosed with tuberculosis, nursing care in recovery is essential.